Does immigration affect native wages? A meta-analysis - Clément Nedoncelle; Léa Marchal; Amandine Aubry; Jérôme Héricourt (Kiel Centre for Globalization (KCG), 2024)
The impact of immigration on native workers' wages has been a topic of long-standing debate. This meta-analysis reviews 42 studies published between 1987 to 2019, offering a comprehensive assessment of reduced-form estimates of the wage effect of immigration. The results confirm that immigration has a negligible effect on native wages. However, a more pronounced wage impact is observable for the U.S. and in recent years. Our analysis underscores the influence of methodological advances and increased data availability in shaping wage effect estimates. Results also highlight the role of the estimator (OLS vs. IV-2SLS, as well as the use of shift-share instruments) in determining the sign and magnitude of the estimated wage effect.
Keywords: C80; J61; J15; J31; 330; Immigration; Labour Market; Meta-Analysis; Wage